2008
DOI: 10.1182/blood-2008-01-131029
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab efficacy and safety in adult splenectomy candidates with chronic immune thrombocytopenic purpura: results of a prospective multicenter phase 2 study

Abstract: IntroductionImmune thrombocytopenic purpura (ITP) is an autoimmune disease characterized by low platelet counts and may be responsible for mucocutaneous bleeding of variable severity. 1 ITP is usually chronic (Ͼ 6 months) in adults and, after this time, the probability of spontaneous remission is low. Standard management is to initiate steroids, anti-Rh 0 (D) immune globulins, and/or intravenous immunoglobulins (IVIgs) for the more severe forms. [2][3][4][5] The response rate is high but most often transient. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
196
7
14

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 236 publications
(231 citation statements)
references
References 35 publications
(55 reference statements)
11
196
7
14
Order By: Relevance
“…This discrepancy could be at least partially explained by ours and Godeau's selection of patients with a lower degree of treatments received before rituximab [19].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This discrepancy could be at least partially explained by ours and Godeau's selection of patients with a lower degree of treatments received before rituximab [19].…”
Section: Discussionmentioning
confidence: 70%
“…The effect of rituximab to safely avoid splenectomy has been also prospectively investigated by Godeau et al [19] in 60 adults with chronic ITP. The authors indicated that, at 2 years, 24 (40%) patients responded to rituximab (i.e., platelet counts 30 3 10 9 /L or more off treatment) avoiding splenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to report that even in these few patients the use of SCIg was effective, safe and well tolerated. The use of the anti-CD20 monoclonal antibody rituximab is expanding in several autoimmune disorders, including rheumatoid arthritis, [31][32][33] immune thrombocy-topenic purpura, 34,35 systemic lupus erythematosus, 36 Sjogren syndrome, anti-neutrophil cytoplasmic antibodyassociated vasculitis, mixed cryoglobulinemia, solid organ transplantation, renal disease, and neurological diseases. 37 Thus, in our Clinical Immunology Unit, a further study is in progress on the putative role of SCIg in the prevention of hypogammaglobulinemia-related infections in nonneoplastic conditions after rituximab therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In immune thrombocytopenia (ITP), B-cell depletion using the lymphoma-type regimen (i.e., at the standard dose, namely 375 mg/m 2 weekly for 4 weeks), is now a second-line off-label therapy in many countries and is used prior to splenectomy, or as a third-line therapy for patients not responding to a splenectomy [3]. In France, based on the findings of a single-arm prospective study [4], RTX is now commonly used in persistent or chronic cases of adult ITP prior to splenectomy. Approximately 40-50% of patients treated with RTX at a standard dose achieve a complete response (CR) by 1 year [5] and 20% have a lasting response at 5 years [6].…”
Section: Introductionmentioning
confidence: 99%